2014
DOI: 10.1016/j.sdentj.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A review of the effect of various ions on the properties and the clinical applications of novel bioactive glasses in medicine and dentistry

Abstract: Bioactive glass is a novel material that dissolves and forms a bond with bone when exposed to body fluids. Bioactive glasses are silicate-based, with calcium and phosphate in identical proportions to those of natural bone; therefore, they have high biocompatibility. Bioactive glasses have wide-ranging clinical applications, including the use as bone grafts, scaffolds, and coating materials for dental implants. This review will discuss the effects of ions on the various compositions of bioactive glasses, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…In medicine, it is commonly being used as a bone graft to promote osteogenesis whereas, in dentistry, it is frequently being used in dentifrices to treat dentin hypersensitivity (DH) and as a coating material of dental implants 33,34 . Few of the common uses ofBGs are explained here.…”
Section: Bio-dental Applications Of Bioactive Glass (Bg)mentioning
confidence: 99%
“…In medicine, it is commonly being used as a bone graft to promote osteogenesis whereas, in dentistry, it is frequently being used in dentifrices to treat dentin hypersensitivity (DH) and as a coating material of dental implants 33,34 . Few of the common uses ofBGs are explained here.…”
Section: Bio-dental Applications Of Bioactive Glass (Bg)mentioning
confidence: 99%
“…Similarly, in primate models, bioactive glass filled bony defects by stimulating osteoproduction. Felipe et al reported that bioactive glass particles were able to treat periodontal defects and triggered the development of mineralized bone in dogs [141,142].…”
Section: Tricalcium Phosphate/hydroxyapatite Biphasic Ceramics (Bcp)mentioning
confidence: 99%
“…It was previously reported that not only does Bioglass® bind to bone but it also facilitates the regeneration of bone. Initially the bone substitute was implanted into humans as a replacement for the ossicles of the middle ear and was subsequently used as a material to repair bone defects eventually including those caused by periodontitis as well (Ali et al, 2014). There are four main methods by which genes involved with osteoblastic proliferation, differentiation, and cell to cell adhesion are upregulated namely: surface chemistry, topography, rate and type of dissolution ions and shear stress at the interface.…”
Section: Class B Bioactive Glassesmentioning
confidence: 99%
“…The original 45S5 Bioglass® contained 45% SiO2, 24.5% Na2O, 24.5% CaO, and 6% P2O55, however, subsequently more research has been conducted into incorporating various therapeutic ions, drugs and growth factors into the glass structure. Table 2 outlines a variety of products that have been incorporated into the glass structure to provide a beneficial effect (Ali et al, 2012;Ali et al, 2014).…”
Section: Therapeutic Ions Drugs and Growth Factorsmentioning
confidence: 99%